Characteristics of patients diagnosed with psychogenic non-epileptic seizures (PNES) who request reinstatement of their driving privileges - Trobliger, Robert; Simpson, Talia; Lancman, Kaleb; Kramska, Lenka; Benbadis, Selim (Epilepsy & behavior, 2025)
RATIONALE: Patients who experience seizures, including PNES, are usually advised to discontinue driving, or have their driving privileges revoked until a determined period of seizure-freedom is achieved. In this retrospective study, patients with PNES who requested driving privileges or reported having resumed driving were compared to those who did not on measures of depression, anxiety, PTSD, and cognitive flexibility/motor speed. METHODS: DiagnosisofPNESwasconfirmedwithvideo-EEG.Demographicand clinical dataand requests for reinstatement of driving privileges (requiring 6 or more months seizure freedom) and reports of decisions to resume driving were noted. Tests of motor speed and hand eye coordination and self-report questionnaires of depression, anxiety and PTSD administered as part of neuropsychological assessment were analyzed. RESULTS: A total of 403 patients with PNES evaluated in 2010-2020 were identified. Of those, 365 patients were eligible for inclusion, and of those, 60 applied for driving privileges or reported that they resumed driving. When the two groups were compared, the group that applied for driving privileges or decided to resume driving was significantly less depressed (p = 0.001) when tested than the group that did not. Furthermore, a significant difference was seen in measures of motor performance between those who requested to resume driving and those who did not (DKEFS T1, p = 0.006, DKEFS T2, p = 0.001, DKEFS T3, p = 0.002, DKEFS T4, p = 0.001; GPT dominant, p = 0.05, GPT non-dominant, p = 0.003). CONCLUSION: Driving a motor vehicle is a useful measure of improvement for PNES because patients with seizures are required to discontinue driving until seizure-freedom is achieved. This study revealed that lower levels of depression and better fine motor functioning were associated with reported seizure-freedom and driving resumption. Depression is commonly associated with diminished performance (slower motor response times and impaired fine motor movements) on tests of motor functioning, both of which may result in less interest in pursuing permission to resume driving. These findings suggest that mood symptoms (and associated performance on measures of motor speed and coordination) may have prognostic significance in patients diagnosed with PNES. This also suggests that timely treatment of depression in newly diagnosed patients with PNES may be indicated.
Keywords: Seizures; Humans; neuropsychologické testy; lidé středního věku; úzkost; psychosomatické poruchy; Conversion Disorder; Female; mladý dospělý; dospělí; záchvaty; Psychophysiologic Disorders; Automobile Driving; lidé; elektroencefalografie; Anxiety; Stress Disorders, Post-Traumatic; Adult; konverzní poruchy; Neuropsychological Tests; řízení motorových vozidel; ženské pohlaví; Male; posttraumatická stresová porucha; Middle Aged; Retrospective Studies; Psychomotor Performance; Young Adult; Electroencephalography; retrospektivní studie; Depression; mužské pohlaví; deprese; psychomotorický výkon